DAMPAK RENOVASI TAMAN WISATA LOANG BALOQ TERHADAP PENYERAPAN TENAGA KERJA DAN PENDAPATAN MASYARAKAT YANG BERAKTIVITAS EKONOMI DI TAMAN WISATA LOANG BALOQ - Fadhlillah, Bagus Rizqy; Daeng, Akung; Wahidin, Wahidin (Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the impact of the Loang Baloq Tourism Park Renovation on the Absorption of Economic Welfare in Loang Baloq Tourism Park. The type of data used in this study is primary data. The population in this study is all employees and traders in Loang Baloq Tourism Park. The data analysis procedure in this study includes a paired t test which was previously carried out to test the normality of the results of the study with the title "The Impact of the Renovation of the Loang Baloq Tourism Park on the Absorption of Labor and Income of the Economically Active Community in the Loang Baloq Tourism Park using the normality test, the paired sample t test (different test), and the wilcoxon test, it can be concluded that the renovation has a positive and significant impact on the income of the community. The test of the research data showed that the renovation had a negative and insignificant impact on the working hours of the community.